Clinical Characteristics and Allergen Sensitization Patterns of Patients with Local Allergic Rhinitis in Southern China - Tao, Xiao Yao; Ng, Chew Lip; Chen, Dong; Lin, Zhi Bin; Wu, Shu Lian; Liang, Mei Jun; Li, Chun Wei; Xu, Rui (International archives of allergy and immunology, 2018)
Local allergic rhinitis (LAR) is characterized by the production of specific IgE (sIgE) in the nasal mucosa without evidence of systemic atopy. The characteristics of LAR in Caucasians have been well documented. LAR is understudied in China, with prevalence, patient demographics, symptomatology, and the allergen sensitization profile being poorly understood. The purpose of this study is to investigate the demographics, characteristics, and allergen sensitization profile of patients with LAR in Southern China. A total of 194 patients with rhinitis and 13 healthy subjects were enrolled in the current study. The patients' demographic data, clinical history, and symptoms were recorded. Local and systemic sIgE to a wide panel of specific allergens were measured in the nasal secretion and serum samples. Among the rhinitis patients, 115 were classified as allergic rhinitis (AR; 59.3%), 15 as LAR (7.7%), and 64 as non-AR (33.0%). The demographic characteristics, duration, frequency, and severity of symptoms were similar, although LAR exhibited higher symptom scores for nasal itch. Monosensitization was the predominant pattern of sensitization in both AR (109 out of 115, 95%) and LAR (14 out of 15, 93%). House dust mite was the dominant allergen in AR patients (109 out of 115, 95%), while pollen was the dominant allergen in LAR patients (11 out of 15, 73%). The prevalence of LAR patients in Southern China was 7.7%. Pollen was the most common sensitizing allergen for the local LAR patients, which differs from Caucasian studies, in which house dust mite was the dominant sensitizing allergen. Monosensitization was the predominant pattern in both AR and LAR.